'Don't let me go! Hold me down!': inspiration, voice and image in Kate Bush's 'Hounds of Love'. Issue 1 (30th November 2015) - Cawood, Ian
Abstract: Although Kate Bush's reputation as a significant musical pioneer has been accepted by most critics and academic commentators since her return to music in 2005, most readings of her work have been highly ahistoric. This paper explores how, with the release of her fifth album, Hounds of Love, in 1985, her popular appeal was widened into a genuine acceptance of her idiom by contemporary cultural commentators. In particular, the paper focuses on the rival inspirations and the shape, form and delivery of the title track, 'Hounds of Love' and its 'alternative' version, released on a 12" disc. The paper concludes by analysing the visual presentation of the song through the promotional video (directed by Bush herself) and her two mimed performances and offering a contextualised explanation for Bush's perceived 'authenticity' as an artist and performer.